Case Report: QARS Deficiency and Favorable Outcome Following Treatment of Seizures With Ketogenic Diet. (March 2017) - Datta, Anita; Ferguson, Alex; Simonson, Chris; Zannotto, Francesca; Michoulas, Aspasia; Roland, Elke; Karnebeek, Clara van; Salvarinova, Ramona
Glutaminyl-tRNA synthetase (QARS) deficiency has been described to be a cause of a neurodegenerative disorder associated with severe developmental delay, microcephaly, delayed myelination, and intractable epilepsy. The epilepsy is thought to be more severe than other tRNA synthetase disorders. Only a few cases have been reported in the literature and there is little information about response to different treatment options. The ketogenic diet is a high-fat, low-carbohydrate diet that is used in treatment resistant epilepsy of various etiologies. There are reports that the diet can also improve neuro-cognitive parameters. The authors report a case of a patient with glutaminyl-tRNA synthetase deficiency and treatment resistant seizures where there was a marked and early favorable response in terms of seizures, alertness and behavior to the ketogenic diet.